Effect of Different Natural Products Against Leaf Blight Diseases of Maize - Debnath, Srabani; Biswas, Sonali (International Journal of Bio-resource and Stress Management, 2023)
This experiment was conducted during kharif seasons (June to September) of 2016 and 2017 at District Seed Farm, Kalyani Simanta of Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India. The objective of the study was to find out the performance of natural products against maydis leaf blight of maize under artificial epiphytotic condition. The eleven natural products were namely; Neem leaves, Karanj leaf, Milkweed / Calotropis leaf, Datura leaf, Parthenium leaf, leaves of Umbelanterna / Lantana camara, leaves of False Ashoka, leaves of tulsi, bulb of garlic, cow urine and Hexaconazole as standard check. The experiment was laid out in Randomized Block Design with 12 treatments with three replications. The extracts of Plant products at 10% concentrations were then applied by spraying to plants in the field just after 24 h of inoculation. 2nd inoculation was done seven days after first inoculation. Severity was calculated for each replication of each treatment by using the Percent Disease Index (PDI). Allium sativum (garlic) bulb @ 10% resulted lowest Percent Disease Index i.e. 28.4% against the Maydis leaf blight and 25.8% against Turcicum leaf blight of maize with the concurrent 61.13% and 65.08% control of diseases. Cow urine @ 50% resulted 29.8% and 28.6% PDI which was statistically equally effective with Allium sativum (garlic) bulb @ 10%. Likewise, this Allium sativum (garlic) bulb @ 10% also produced highest yield (2910 kg ha-1) which was 34 higher than the chemical, Hexaconazol used for these diseases.